Hubungan Antara Kehilangan Gigi Posterior Dengan Kliking Sendi Temporomandibular Berdasarkan Jenis Kelamin di Klinik Prostodonsia Rumah Sakit Gigi dan Mulut Universitas Jember (Relationship Between Tooth Loss Posterior With Temporomandibular Joints Klikin - Adilah Novarani Dwipayanti; R. Rahardyan Parnaadji; Kiswaluyo Kiswaluyo (Pustaka Kesehatan, 2016)
Loss of posterior teeth will result in a change of balance resulted in occlusion disharmony. Thishas also resulted in the temporomandibular joint, so it will happen kliking. The aim of this studywas to determine the relationship between loss of posterior teeth with temporomandibular jointclicking by gender in auscultation in patients at Prosthodontics Clinic of the Hospital University ofJember. This type of research was observational research clinic. Research done by examinationauscultation with a stethoscope tool that has been modified was the head stethoscope replacedwith saliva ejector tip called "sound scope". The results of data analysis used Chi-Square Testshows that tooth loss had no relation (p>0,05) to whether or not there kliking temporomandibularjoint. Based on gender, women were more susceptible to kliking temporomandibular joint thanmen.Keywords: Loss of posterior teeth, temporomandibular joint clicking, clicking, gender